Epidemiology of Toxoplasma gondii infection in pregnant women in Armenia, Quindío, Colombia (Colombia Medica, 1993)
From January 1988 to September 1990, 1,617 pregnant women attended health centers in Armenia, Quindío, and Colombia. An indirect immunofluorescence antibody technique for IgG anti-toxoplasma was used. It was found 63.3% of sero-positivity, which was greater with risk factors: 67. 7% when cat contact was detected, 73.6% if the contact was close (P